Digital Eco-Brand Strategy of FMCG Companies as a Means of Attracting Loyal Audience - Siazin, Sergii; Popov, Andrii; Melyan, Hripsime; Bilous, Anastasiia; Oznobishyna, Maryna (International Review of Management and Marketing, 2026)
The significance of this study is underscored by the increasing necessity for FMCG enterprises to integrate digital eco-brand strategies into their operational frameworks to enhance consumer loyalty amid an intensively competitive global environment. The primary objective of this research is to conduct a thorough evaluation of the influence exerted by digital eco-brand strategies on cultivating trust and sustaining consumer loyalty in an international context. The research methodology is predicated on an analysis of panel data from ten leading international FMCG companies spanning the years 2020 to 2024. This comprehensive approach facilitated the evaluation of both economic metrics and behavioral dimensions. The novelty of this work resides in formulating the integrated Digital Eco Brand Index (DEBI) strategy and its combination with the consumer loyalty index. The findings elucidate that DEBI exerts a consistently positive influence on loyalty (β≈0.17–0.22), with the effect doubling upon surpassing the threshold of 0.6. Trust serves as a vital mediator, transmitting over 40% of this impact, while the phenomenon of greenwashing considerably undermines loyalty. Event analysis corroborated that large-scale campaigns in 2022 elevated the loyalty index by 0.17 standard deviations. Notably, the most significant growth was exhibited by Unilever (+0.66), Reckitt (+0.55), Henkel (+0.47), and Nestlé (+0.44). The conclusions validate the fulfillment of all research objectives and affirm the importance of digital eco-brand strategies within the FMCG sector.